Determining the Concentrations of Elements in Tobacco Selected in Iraqi Markets Using X-Ray Fluorescence Technique - Alsaide, Jamal K.; Hasan, Nada M.; Khudhur, Fadi H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
X-rays fluorescence technology was used to measure the concentrations of trace and toxic elements in tobacco smoke. One sample local and eight samples were imported selected from Iraqi markets. The results proved that tobaccos contain few concentrations of element (calcium, potassium, sodium, manganese, magnesium, chlorine, and sulfur), trace concentrations of element (aluminum, vanadium, iron, cobalt, nickel, copper and zinc), and toxic concentrations of element (arsenic, selenium, bromine, antimony, cadmium, mercury and lead). Results are proved the concentrations of elements of samples are lower levels with the other countries in few element like (calcium, potassium, sodium and manganese), while the other elements were highest than the other countries.